2020
DOI: 10.1109/access.2020.2972905
|View full text |Cite
|
Sign up to set email alerts
|

A Kernel-Width Adaption Diffusion Maximum Correntropy Algorithm

Abstract: Impulsive noises are widely existing in various systems like noise cancellation system and wireless communication systems, where adaptive filtering (AF) is always employed to identify specific systems. Additionally, the impulsive noises will affect the performance for estimating these systems, resulting in slow convergence or worse identification accuracy. In this paper, a diffusion maximum correntropy criterion (DMCC) algorithm with adaption kernel width is proposed, denoting as DMCC adapt algorithm, to find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Therefore, when applying a given algorithm in practice, one should use the estimates of these parameters. However, the estimates derived from (40) to (42) allow the researcher to pre-evaluate the limits of a given algorithm and the effectiveness of its application when solving practical tasks.…”
Section: Discussion Of Results Of Studying the Convergence Of A Multimentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, when applying a given algorithm in practice, one should use the estimates of these parameters. However, the estimates derived from (40) to (42) allow the researcher to pre-evaluate the limits of a given algorithm and the effectiveness of its application when solving practical tasks.…”
Section: Discussion Of Results Of Studying the Convergence Of A Multimentioning
confidence: 99%
“…Numerous studies [36][37][38][39][40][41][42][43][44] have shown that with non-Gaussian noise in measurements an informational approach is very effective. At the same time, the criterion used should take into consideration the statistics of the error signal not only of the second but also of a higher order.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…A robust DE method based on MCC, called diffusion MCC (DMCC), was developed in [15] to mitigate the robustness of the traditional DAF algorithms. In addition, a proportional DMCC algorithm with adaptable kernel width was proposed for sparse distributed system identification in the cases of impulse noise [16]. The diffusion subband adaptive filtering (DSAF) algorithm, based on symmetrical MCC with individual weighting factors, was developed for colored input signals [17].…”
Section: Introductionmentioning
confidence: 99%